Effect of flame temperature on structure and CO oxidation properties of Pt/CeO2 catalyst by flame-assisted spray pyrolysis - Naoya Minegishi; Peizhou Li; Tsuyoshi Nagasawa; Hidenori Kosaka (Applications in Energy and Combustion Science)
Flame synthesis offers the potential for the synthesis of structure-controlled catalysts. In this study, Pt/CeO2 nanoparticles were synthesized via flame-assisted spray pyrolysis (FASP) and used as CO oxidation catalysts. The catalysts were synthesized using a burner diffusion flame at three different flame temperatures (maximum flame temperatures, Tf = 1556, 1785, and 2026 K), and their particle structure and CO oxidation activity were evaluated. The synthesized Pt/CeO2 catalysts had a bimodal structure containing 100 nm-scale CeO2 loaded with 10 nm-scale Pt and fine CeO2 < 10 nm loaded with highly dispersed Pt (less than 1 nm). As the flame temperature increases from 1556 to 2026 K, the formation of fine CeO2 particles dominates, resulting in an increase in BET specific surface area from 7.97 to 112 m2/g and Pt dispersion from 4.67 to 20.6%. Insight into the particle formation routes that determine the catalyst structure is provided by numerical simulation of droplet evaporation in a burner flame. CO oxidation experiments showed that the temperature at which CO conversion reached 100% (T100) decreased from 513 to 378 K with increasing flame temperature in FASP. In addition, the thermal stability test showed that the Pt dispersion after thermal degradation was higher for Pt/CeO2 catalyst made by FASP at Tf = 2026 K than that prepared by the impregnation method, and the T100 for CO oxidation was lower by 20 K.